Exploring the Relationship Between Social Media Use and Symptoms of Depression and Anxiety Among Children and Adolescents: A Systematic Narrative Review - Saleem, Naila; Young, Paul; Yousuf, Saman (Cyberpsychology, behavior and social networking, 2024)
Social media use is ubiquitous to the lives of children and adolescents. The body of research investigating its potential impact on mental health has risen exponentially. We systematically reviewed the present literature exploring potential linkages between social media use and symptoms of depression and anxiety in this vulnerable group. Using the Preferred Reporting Items for Systematic Reviews and Meta-analyses framework, articles were searched across Medline, EMBASE, CINAHL, and PsycINFO databases from inception to February 2024. Quantitative studies with social media as exposure and anxiety/depressive symptoms as outcomes in children and adolescents 5-18 years of age were included. Of the 4850 studies retrieved, 67 fulfilled the inclusion criteria. The most frequent measures of social media were "time spent on social media" and "frequency of use." Depressive symptoms were the outcome of 61 studies, whereas anxiety was measured in 27 studies. Most studies were of fair quality ( = 53). A meta-analysis was not possible due to study heterogeneity. Our review shows that (1) problematic social media use is associated with depressive and anxiety symptoms among children and adolescents, (2) duration of social media use was more consistently linked with anxiety and depression in girls compared with boys, and (3) mediating and moderating mechanisms were sleep deprivation, social comparison, and feedback-seeking behaviors, exercise, social support, and type of social media use. Qualitative work and robust large-scale longitudinal observations using a person-specific approach are needed to further our understanding of the impact of social media use on depression and anxiety in children and adolescents.